2010
DOI: 10.1227/01.neu.0000365264.99133.ca
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Choroid Plexus Cauterization Versus Ventriculoperitoneal Shunt for Hydranencephaly and Near Hydranencephaly

Abstract: ECPC is an acceptable alternative to VPS for treatment of hydranencephaly and near hydranencephaly. It is a single, definitive, safe, effective, and economical treatment that may avoid the complications of shunting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 20 publications
0
28
0
2
Order By: Relevance
“…1 The prospective study reported by Malheiros et al compared CPC with VP shunt placement in 17 infants with either hydranencephaly or near-hydranencephaly. 3 CPC successfully controlled head size in 8 of 9 infants. Of 7 children treated with VP shunts, 2 required shunt revisions during follow-up.…”
Section: Discussionmentioning
confidence: 90%
“…1 The prospective study reported by Malheiros et al compared CPC with VP shunt placement in 17 infants with either hydranencephaly or near-hydranencephaly. 3 CPC successfully controlled head size in 8 of 9 infants. Of 7 children treated with VP shunts, 2 required shunt revisions during follow-up.…”
Section: Discussionmentioning
confidence: 90%
“…Hydranencephaly is a malformation of the central nervous system that results from errors of embryonic development post-neuralation (5). It has been proposed that the embryonic occlusion of the carotid arteries is the probable etiology of the disease based on the finding that only those structures supplied by posterior cerebral arteries form (3).…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that the embryonic occlusion of the carotid arteries is the probable etiology of the disease based on the finding that only those structures supplied by posterior cerebral arteries form (3). The major and defining characteristics of hydranencephaly include an almost or complete lack of cortical mantle, specifically the cerebral hemispheres (3,5,8). It is generally accepted that in hydranencephaly, if there is any remaining cortex present, it will not be functioning (6,9).…”
Section: Introductionmentioning
confidence: 99%
“…We wish to point out that one of the larger series of choroid plexus coagulation (CPC) for hydranencephaly or near hydranencephaly [2] was not identified in their literature search and was not mentioned. This occurred because the terminology used for CPC in our prior report was endoscopic choroid plexus cauterization (ECPC) rather than coagulation.…”
mentioning
confidence: 99%
“…Nonetheless, we think the readers of the current review should be aware of our study [2], wherein we prospectively randomized infants with hydranencephaly and near hydranencephaly to have either ECPC or ventriculoperitoneal shunt (VPS). Of 17 patients, ten were randomized to receive ECPC.…”
mentioning
confidence: 99%